The Treatment of Rhodiola Mimics Exercise to Resist High-Fat Diet-Induced Muscle Dysfunction via Sirtuin1-Dependent Mechanisms - You, Baiyang; Dun, Yaoshan; Fu, Siqian; Qi, Dake; Zhang, Wenliang; Liu, Yuan; Qiu, Ling; Xie, Murong; Liu, Suixin (Frontiers in Pharmacology, 2021)
Muscle dysfunction is a complication of high-fat diet (HFD)-induced obesity that could be prevented by exercise, but patients did not get enough therapeutic efficacy from exercise due to multiple reasons. To explore alternative or supplementary approaches to prevent or treat muscle dysfunction in individuals with obesity, we investigated the effects of Rhodiola on muscle dysfunction as exercise pills. SIRT1 might suppress atrogenes expression and improve mitochondrial quality control, which could be a therapeutic target stimulated by exercise and Rhodiola, but further mechanisms remain unclear. We verified the lipid metabolism disorders and skeletal muscle dysfunction in HFD feeding mice. Moreover, exercise and Rhodiola were used to intervene mice with a HFD. Our results showed that exercise and Rhodiola prevented muscle atrophy and dysfunction in obese mice and activating the SIRT1 pathway, while atrogenes were suppressed and mitochondrial quality control was improved. EX-527, SIRT1 inhibitor, was used to validate the essential role of SIRT1 in salidroside benefit. Results of cell culture experiment showed that salidroside alleviated high palmitate-induced atrophy and mitochondrial quality control impairments, but these improvements of salidroside were inhibited by EX-527 in C2C12 myotubes. Overall, Rhodiola mimics exercise that activates SIRT1 signaling leading to improvement of HFD-induced muscle dysfunction.